Kyphoplasty Technique for Thoraco-Lumbar Compression Fracture - Alfred Sutrisno Sim (Neurologico Spinale Medico Chirurgico, 2018)
Osteoporotic vertebral compression fracture (VCF) is a significant causeof morbidity and mortality among elderly patients. Fractures canhappen because of osteoporosis, tumors, or other conditions.In the past two decades, kyphoplasty has emerged as surgicaloptions that play a central role in the treatment of vertebralcompression fractures. Before the common use of kyphoplasty, theprincipal surgical option for treatment of compression fractures wasdecompression and fusion. However, surgical fixation frequentlyfailed in elderly patients because of osteopenia. Kyphoplastyhas expanded to include treatment of osteoporotic compressionfractures, traumatic compression fractures, and metastaticcompression fractures. Osteoporotic compression fractures are nowthe most common indication for this procedure.Kyphoplasty utilizes an inflatable balloon to create a cavityfor the cement with the additional potential goals of restoringheight and reducing kyphosis. Kyphoplasty is an effectivetreatment options for the reduction of pain associated withvertebral body compression fractures. Biomechanical studiesdemonstrate that kyphoplasty is initially superior for increasingvertebral body height and reducing kyphosis, but these gainsare lost with repetitive loading. Complications secondaryto extravasation of cement include compression of neuralelements and venous embolism. These complications are rarebut more common with vertebroplasty. Kyphoplasty is a safeand effective procedure for the treatment of vertebral bodycompression fractures.